Coaching Influence, Communication, and Accountability: Developing Leadership Behaviors in Every Nurse - Patricia “Pidge” Lohr (The Journal of Continuing Education in Nursing, 2026)
Coaching is a powerful strategy for developing leadership behaviors in nurses. Distinct from mentoring and precepting, coaching uses purposeful communication and reflective questioning to foster critical thinking, accountability, and influence. Nurse educators can integrate coaching into everyday interactions to strengthen clinical judgment, psychological safety, professional growth, and patient care. Leadership is an essential competency for every nurse. Nurse educators are uniquely positioned to cultivate leadership behaviors by coaching nurses to influence others, communicate effectively, and embrace accountability. This work begins during onboarding and nurse residency and continues through competency validation and ongoing professional development, complementing succession planning by building leadership capacity at every level of the organization.